Tectonic Implications of Detrital Zircon Ages From Lesser Himalayan Mesozoic‐Cenozoic Strata, Pakistan. (20th May 2018) - Qasim, Muhammad; Ding, Lin; Khan, Muhammad Asif; Jadoon, Ishtiaq A. K.; Haneef, Muhammad; Baral, Upendra; Cai, Fulong; Wang, Houqi; Yue, Yahui
Abstract: We carried U‐Pb‐Hf geochronology of the clastic sequence covering upper Mesozoic‐Cenozoic period. The upper Mesozoic sequence is overlain unconformably by the Cenozoic strata, marking regional K‐T boundary, which is mapped as angular unconformity. This angular relationship may strongly indicate a compressional orogenic event that occurred during the Late Cretaceous. Late Cretaceous Kohistan‐Karakoram collision and ophiolite emplacement may account for the development of this compression along the northern Indian margin. The U‐Pb‐Hf isotopic analyses of the upper Mesozoic and lower Cenozoic sequence (Hangu Formation and Lower Patala Formation) are similar to the Tethyan and Lesser Himalayan signatures, which indicate the Indian‐plate provenance. The two younger Cretaceous grains recorded in the Hangu Formation might be derived from the Indian‐plate volcanic rocks and/or Tethyan Himalayan volcanic rocks. The absence of ophiolitic age component in the precollision sequence may indicate that these ophiolites are not exposed until final India‐Eurasia collision. The major shift in provenance is recorded in the upper part of the Patala Formation, where the presence of disconformity and the appearance of <100 Ma detrital zircons indicate the contribution of Eurasian source (i.e., Kohistan‐Ladakh arc; KLA), which is further supported by the ɛHf(t) signatures. Upsection, the contribution from Eurasian source increased in the Early Middle Eocene Kuldana Formation. Therefore, we suggest that the provenance mixing close to Paleocene‐Eocene boundary indicates that the India‐Eurasia collision in the north Pakistan occurred at ∼56–55 Ma and subsequent exhumation increased the contribution of the northern (Eurasian) provenance in the upsection. Key Points: First Late Jurassic‐Cretaceous detrital zircon U‐Pb‐Hf data set in northwestern Himalaya, Pakistan Angular unconformity at K‐T boundary may favors compression related to Kohistan‐Karakoram collision and ophiolite emplacement The Cenozoic U‐Pb‐Hf data precisely constrain timing of India‐Eurasia collision at 56–55 Ma